Epilepsy with auditory features: Long‐term outcome and predictors of terminal remission. (21st February 2018) - Bisulli, Francesca; Menghi, Veronica; Vignatelli, Luca; Licchetta, Laura; Zenesini, Corrado; Stipa, Carlotta; Morigi, Francesca; Gizzi, Matteo; Avoni, Patrizia; Provini, Federica; Mostacci, Barbara; d'Orsi, Giuseppe; et al.
Summary: Objective: To assess the long‐term outcome of epilepsy with auditory features (EAF) and to identify the clinical predictors for prognosis. Methods: The study involved consecutive EAF patients with a follow‐up of ≥5 years. Terminal remission (TR) was defined as a period of ≥5 consecutive years of seizure freedom at the last follow‐up. We used Kaplan‐Meier estimate to calculate the cumulative time‐dependent probability of conversion to TR. Log‐rank test and multivariate Cox regression analyses were performed to study the association between time to TR and prognostic determinants. Results: We included 123 EAF patients (male/female = 58/65) with a median follow‐up of 11 years (1626.9 person‐years). Most were sporadic cases (68.3%), whereas 31.7% reported a family history of epilepsy. At last assessment, 42 patients had achieved TR (34.1%). Of the remaining 81 cases with no TR (65.9%), 37% had been in remission for 1‐4 years and 62.9% still had seizures within the past year. The cumulative rates of TR were 26.6%, 35.7%, and 51.6% at 10, 20, and 30 years from inclusion. On multivariate analysis, age at onset > 10 years (hazard ratio [HR] = 3.2, P = .028), auditory aura characterized by distortions only versus simple/complex hallucinations (HR = 2.9, P = .041), and unremarkable scalp electroencephalogram (EEG) versus EEG with focal epileptiform activity (HR = 3.5, P = .041) were associated with TR. Significance: Our data show a wide prognostic spectrum of EAF, ranging from mild forms with spontaneous remission, to severely refractory epilepsy addressed to surgery. The outcome, less favorable than expected from previous studies, appears to be primarily a function of 3 prognostic negative risk factors: age at onset < 10 years, auditory aura characterized by complex auditory hallucinations, and focal epileptiform abnormalities on scalp EEG. These predictors, easy to collect even at the first visit, may inform both clinicians and patients about the long‐term prognosis and aid patient management.